Effect of work boot type on work footwear habits, lower limb pain and perceptions of work boot fit and comfort in underground coal miners. (April 2017) - Dobson, Jessica A.; Riddiford-Harland, Diane L.; Bell, Alison F.; Steele, Julie R.
Abstract: Lower limb injuries are highly prevalent in underground coal mining. Wearing gumboots with inadequate ankle support was thought to contribute to these injuries. Despite the uptake of leather lace-up boots, which provide more ankle support, no recent research could be found investigating the effect of this alternative work boot in underground coal mining. Consequently, this study aimed to determine whether boot type (gumboot, leather lace-up boot) influenced work footwear habits, foot problems, lower limb pain, lower back pain, or perceptions of work boot fit and comfort in underground coal miners. Chi-squared tests were applied to 358 surveys completed by underground coal miners to determine whether responses differed significantly ( p < 0.05) according to boot-type. There were no significant between-boot differences in regards to the presence of foot problems, lower limb pain or lower back pain. However, the types of foot problems and locations of foot pain differed according to boot type. Gumboot wearers were also more likely to state that their work boot comfort was either 'uncomfortable' or 'indifferent', their work boot fit was 'poor' and their current boot did not provide enough support. The introduction of more structured leather lace-up boots appears to have positively influenced the support and fit provided by mining work boots, although foot problems, lower limb pain and lower back pain continue to be reported. Further investigation is recommended to identify which specific boot design features caused these observed differences in work boot fit, comfort and locations of foot pain and how these design features can be manipulated to create an underground coal mining work boot that is comfortable and reduces the high incidence of foot problems and lower limb pain suffered by underground coal miners. Highlights: Chi-squared tests were applied to 358 surveys completed by underground coal miners. Boot type did not influence lower limb and lower back pain incidence. Work boot design differences influence the types of foot problems and locations of foot pain A more structured leather lace-up boot positively influenced perceptions of ankle support, fit and comfort. Waterproofing and adequate ankle support were two design features that would make an ideal work boot more comfortable.